Lower extremity injuries in gymnasts - Katz, N. B.; Casey, E.; Gagliardi, A. G.; Albright, J. C. (Gymnastics medicine - evaluation, management and rehabilitation, 2020)
The physical demands of gymnastics place extreme loads on many regions of a gymnast`s body. Prior research demonstrates a higher prevalence of lower limb injuries (54.1-70.2%) comparcd to upper limb injuries (17.1-25.0%) in gymnasts. This trend was observed during the last three Olympic Games (2008, 2012, and 2016), where the majority of gymnastic injuries were in the lower limbs (63%) compared to the trunk (23%) or upper limbs (14%). This trend is also seen in subelite, collegiate, and adolescent gymnasts; injuries to the lower limbs were found to be the most common, followed by injuries to the upper limbs, spine, and trunk. Moreover, a recent study assessing all reportcd injuries in NCAA women`s gymnastics between 2009 and 2014 revealed that half were to the lower limbs. For these reasons, a complete understanding of the most common lower limb injuries and the best course of treatment is necessary to provide the optimal medical care.